Does Okun’s Law explain the relationship between economic growth and unemployment in Nigeria? - Dankumo, Ali Madina; Suryati Ishak; Oluwaseyi, Zubair Azeem; Onisanwa, Idowu Daniel (Penerbit Universiti Kebangsaan Malaysia, 2019)
Okun (1962) statistically established a negative association between growth and unemployment. This is known as Okun’s Law. This paper investigates, if Okun’s law holds in Nigeria considering the nature of its system of governance, and the study employs an ARDL bounds test approach using data covering the period of 22 years between 1996 and 2017. The results show that unemployment, efforts to reduce corruption and political stability have a negative relationship with growth, although only political stability is significant, whereas, unemployment and corruption are not. The role control of corruption and political stability are contrary to the expected effect which was a positive one. This result is thus contrary to Okun’s law, which states that “1% decrease in unemployment will lead to 2% increase in GDP”, even though the relationship is shown to be negative. Measures and policies to enhance stable and conducive environments were recommended.